2014
DOI: 10.1136/annrheumdis-2013-204588
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of conventional synthetic disease-modifying antirheumatic drugs, glucocorticoids and tofacitinib: a systematic literature review informing the 2013 update of the EULAR recommendations for management of rheumatoid arthritis

Abstract: ObjectivesTo update a previous systematic review assessing the efficacy of conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) in rheumatoid arthritis (RA).MethodsTwo systematic reviews of the literature using PubMed, Embase and the Cochrane library were performed from 2009 until January 2013 to assess the efficacy of csDMARDs (as monotherapy or combination therapy) in adults with RA, and the efficacy of glucocorticoids in early RA. A third systematic review was performed until March 2013 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 45 publications
2
71
0
15
Order By: Relevance
“…Several systematic reviews have concluded that low dose (B7.5 mg/day) GC can provide a useful ''bridgingtherapy'' below the therapeutic effects of the slower acting DMARDs start to manifest [60][61][62][63]. Conclusion accepted by EULAR in their 2010 recommendations [64] and further confirmed in 2014 [65]. The ACR has been rather more reticent on the use of GCs and in its 2012 update of recommendations, focussed on conventional DMARDs and biological therapies and did not address the use of GCs [66].…”
Section: Gc Therapeutic Strategies In Ramentioning
confidence: 94%
“…Several systematic reviews have concluded that low dose (B7.5 mg/day) GC can provide a useful ''bridgingtherapy'' below the therapeutic effects of the slower acting DMARDs start to manifest [60][61][62][63]. Conclusion accepted by EULAR in their 2010 recommendations [64] and further confirmed in 2014 [65]. The ACR has been rather more reticent on the use of GCs and in its 2012 update of recommendations, focussed on conventional DMARDs and biological therapies and did not address the use of GCs [66].…”
Section: Gc Therapeutic Strategies In Ramentioning
confidence: 94%
“…Впоследствии в серии РПКИ [23][24][25][26][27][28][29][30], их метаанализе [32][33][34] и систематических обзо-рах [35,36] было доказано, что применение ГК (в комби-нации с БПВП) способствует более выраженному тормо-жению деструкции суставов по сравнению с монотерапи-ей БПВП, по крайней мере при раннем РА. При этом структурно-модифицирующий эффект ГК сохраняется в течение длительного времени после отмены ГК [37][38][39][40].…”
Section: эффек тивностьunclassified
“…МТ -эффективный («якорный») препарат для лече-ния РА, который применяется как в виде монотерапии, так в комбинации с ГК, стандартными БПВП и ГИБП [36,37]. Монотерапия МТ (в сочетании с ГК или без них) эффек-тивна у 30-60% пациентов [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: рисunclassified